1974
DOI: 10.1901/jeab.1974.22-115
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECTS OF NUMBER OF RESPONSES ON PAUSE LENGTH WITH TEMPORAL VARIABLES CONTROLLED1

Abstract: A change in the size of a fixed-ratio schedule involves a simultaneous change in number of responses, in time to complete the ratio (work time), and in the interval between successive reinforcements (interreinforcement interval). Previous studies have suggested the importance of work time and the interreinforcement interval in controlling the length of the post-reinforcement pause. The present study sought to determine whether number of responses is also a significant factor. Pigeons were trained on a multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1
1

Year Published

1977
1977
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 8 publications
1
19
1
1
Order By: Relevance
“…Log-transformed data from the Crossman et al (1974) Psychological Reports, 1973Reports, ,32,1925Reports, -1928 also observed this effect (e.g ., Barowsky & Mintz, 1978), and it undoubtedly contributes to some of the variability in the present observations. Finally, Figure 3 presents the data collected in the Ball State University laboratories (log transformations of the median pause from the last five sessions at a ratio size).…”
Section: Methodsmentioning
confidence: 76%
“…Log-transformed data from the Crossman et al (1974) Psychological Reports, 1973Reports, ,32,1925Reports, -1928 also observed this effect (e.g ., Barowsky & Mintz, 1978), and it undoubtedly contributes to some of the variability in the present observations. Finally, Figure 3 presents the data collected in the Ball State University laboratories (log transformations of the median pause from the last five sessions at a ratio size).…”
Section: Methodsmentioning
confidence: 76%
“…Thus, the optimal strategy on FR, as on fixed-T RID, is to respond immediately after food. However, in both cases animals wait before responding and, as one might expect based on the assumption of a roughly constant interresponse time on all ratio schedules, the duration of the wait on FR is proportional to the ratio requirement (Powell 1968), although longer than on a comparable chain-type schedule with the same interreinforcement time (Crossman et al 1974). The phenomenon of ratio strain-the appearance of long pauses and even extinction on high ratio schedules (Ferster & Skinner 1957)-may also have something to do with obligatory linear waiting.…”
Section: Temporal Dynamics: Linear Waitingmentioning
confidence: 87%
“…In other words, we propose that indifference between schedules that require responding and those that do not is the exception, not the rule (cf. Crossman, Heaps, Nunes, & Alferink, 1974).…”
Section: Discussionmentioning
confidence: 99%